SOSIALISASI PARTISIPASI PEMILIH PEMULA PADA PILKADA TINGKAT KABUPATEN BEKASI DI DESA WIBAWAMULYA - Wulandari, Delvi; Suryani, Elvira; Rofieq, Ainur (An-Nizam, 2024)
New voters are young people who are exercising their right to vote for the first time, generally consisting of students, college students or voters aged 17-21 years. Based on observations, community participation in Wibawamulya Village towards the political process is very low. Thus, the author is interested in conducting this program, which aims to educate and provide an understanding of the importance of their involvement in the political process, as well as providing an understanding of how to make rational choices, because their participation and votes are not just rights, but also obligations that are certainly able to bring changes in the future to create a better government. This program is implemented through socialization by means of seminars or discussions, with the hope of providing understanding to beginners about the importance of voting rights and how to choose wisely. Based on the evaluation results, if seen from the previous data after the socialization of community service activities, it has succeeded in increasing the understanding and interest of novice voters to participate more in the political process, one of which is in the upcoming 2024 Pilkada process.